2013
DOI: 10.1002/ppul.22796
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of exhaled nitric oxide in healthy children 1–5 years using off‐line tidal breathing

Abstract: Measurement of the fraction of exhaled nitric oxide (FeNO) is a useful test to diagnose and/or monitor eosinophilic airway inflammation. The off-line tidal breathing method is used for measurements in young children, but reference values for preschool children are scarce. The objective of this study was to establish reference values for FeNO in healthy children 1-5 years old. We included 51 healthy children (23 males), mean age 32.5 months, from the general population and measured FeNO, using an off-line tidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 20 publications
0
32
1
3
Order By: Relevance
“…Sedentary behavior such as television viewing and video games has also been associated with increased FeNO levels in one study that adjusted for indoor allergen exposure, body mass index and allergic sensitization [22]. In children aged 1–5 years, FeNO has been shown to be unaffected by gender, age, weight or height [23]. One study of infants aged 4–26 months showed that maternal history of asthma was associated with elevated FeNO [24].…”
Section: Factors That Influence Fenomentioning
confidence: 99%
“…Sedentary behavior such as television viewing and video games has also been associated with increased FeNO levels in one study that adjusted for indoor allergen exposure, body mass index and allergic sensitization [22]. In children aged 1–5 years, FeNO has been shown to be unaffected by gender, age, weight or height [23]. One study of infants aged 4–26 months showed that maternal history of asthma was associated with elevated FeNO [24].…”
Section: Factors That Influence Fenomentioning
confidence: 99%
“…(40) Although it has been used for older children and adults for several decades, only recently has FENO been shown to be systematically reproducible in preschool and school-aged children. (41,42) With offline analysis, reference values have begun to be established for children as young as 12 months of age, whereas online analysis, typically used in older children and adults, requires a constant flow of 50 mL/sec. (42) In 3-7-year-old asthmatics, FENO did not correlate to FEV 1 , FEV 1 :FVC (forced vital capacity) ratio, or FEF 25:75 (forced expiratory flow), but there was a significant correlation with allergy skin tests, (41) recurrent wheezing, (43) and serum immunoglobulin E, peripheral blood eosinophilia, and eosinophilic cationic protein.…”
Section: Exhaled Nitric Oxidementioning
confidence: 99%
“…(41,42) With offline analysis, reference values have begun to be established for children as young as 12 months of age, whereas online analysis, typically used in older children and adults, requires a constant flow of 50 mL/sec. (42) In 3-7-year-old asthmatics, FENO did not correlate to FEV 1 , FEV 1 :FVC (forced vital capacity) ratio, or FEF 25:75 (forced expiratory flow), but there was a significant correlation with allergy skin tests, (41) recurrent wheezing, (43) and serum immunoglobulin E, peripheral blood eosinophilia, and eosinophilic cationic protein. (44) FENO has been shown to correlate with health outcomes in asthma; in one study, the cohort monitored by FENO had an increased use of leukotrienes and inhaled corticosteroids and decreased exacerbation frequency compared with the control group.…”
Section: Exhaled Nitric Oxidementioning
confidence: 99%
“…453 An elevated FENO, recorded >4 weeks from any URTI in pre-school children with recurrent coughing and wheezing, may predict physician-diagnosed asthma by school age. 454 FENO testing is not widely available.…”
Section: Exhaled Nitric Oxidementioning
confidence: 99%